Psychological diagnostics of risky behavior of adolescents - Rakhimkulova, Anastasiia (Psychiatry, Neurology and Medical Psychology, 2018)
The article reflects practical results of the research on adolescent risky behavior and specifically – the psychodiagnostics stage. Traditionally therapeutic impact on risky adolescents is not quite effective. We assume that the main reason of poor efficiency of the psychological correction of risky behavior lies in the inability to address precise factors that stand out for particular adolescent since these factors may vary substantially. In our research we were able to distinguish three factors and their wide array of components that affect adolescent’s engagement into such types of behavior. Grounding on those we elaborated a detailed procedure for running psychological diagnostics that enables to identify and to further impact actual psychological targets during further coming psychological correction classes. The psychodiagnostics procedure aims at analyzing the following phenomena: adolescent’s predisposition to self-harming and suicidal behavior; current pshyco-emotional state; attitude to self and its components; stress-resilience; typical coping strategies and psychological adaptation. The proposed system of methods also enables to identify every adolescent’s strengths that a psychotherapist can employ as the basis for new skills’ development.